2005
DOI: 10.1111/j.1467-7652.2005.00154.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐yield production of authentic human growth hormone using a plant virus‐based expression system

Abstract: SummaryWe describe here a high-yield transient expression system for the production of human growth hormone (hGH, or somatotropin)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
82
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(91 citation statements)
references
References 36 publications
4
82
0
2
Order By: Relevance
“…In comparison with our CMV system, CMV would be easier in preparation for an inoculum but agroinfiltration would be better in infection efficiency. They also succeeded in high-yield production (10% of soluble protein) of active human growth hormone using the same system (Gils et al 2005). However, in this system, they extracted the expressed protein from the Agrobacteirum-infiltrated areas before the tissues died.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In comparison with our CMV system, CMV would be easier in preparation for an inoculum but agroinfiltration would be better in infection efficiency. They also succeeded in high-yield production (10% of soluble protein) of active human growth hormone using the same system (Gils et al 2005). However, in this system, they extracted the expressed protein from the Agrobacteirum-infiltrated areas before the tissues died.…”
Section: Discussionmentioning
confidence: 95%
“…For example, we can mass-produce therapeutic proteins in their active forms in edible plants, enabling the oral-delivery of protein drugs (Arazi et al, 2001;Ma et al, 2005). Currently, heterologous genes can be expressed in plants using either transgenic plants or plant viral vectors (Matsumura et al, 2000;Menassa et al, 2000;Gils et al, 2005). The disadvantages of transgenic plants reside in the system itself; the method is time-consuming and an efficient transformation system is lacking for many plants.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the chloroplast targeting sequence may act as a translational enhancer, and/or it could be protecting nascent proteins from degradation in the cytosol (Jang et al, 1999). A recent report indicated that accumulation of a human growth hormone protein increased when it was targeted to apoplast, rather than to the chloroplast (Gils et al, 2005). Interestingly, a high level of viral RNAs was present at 18 d.p.i.…”
Section: Discussionmentioning
confidence: 99%
“…24 MagnICON, a TMV-based viral provector system developed by Icon genetics, 25 has shown great promise in rapid production of large quantities of various recombinant proteins. [26][27][28][29][30] Using this system, we have achieved high yield (5-10% TSP) production of PyMSP4/5, which was highly stable at ambient temperature after freeze-drying and was immunogenic following oral administration in mice. 31 Since Mason et al reported the successful expression of HBsAg in transgenic tobacco, which demonstrated the promise of using transgenic plants as low-cost vaccine production systems, 32 the concept of plant-produced vaccine has changed from "edible vaccines" to "heat-stable oral vaccines" or low-cost injectable vaccines.…”
mentioning
confidence: 99%